IoT Enabled Quality of Experience Measurement for Next Generation Networks in Smart Cities. (September 2020) - Saadi, Muhammad; Noor, Muhammad Talha; Imran, Aadil; Toor, Waqas Tariq; Mumtaz, Shahid; Wuttisittikulkij, Lunchakorn
Highlights: Experimental demonstration hardware-software co-designed Quality of Experience (QoE) Management Solution which capable of monitoring and reporting the web, video, VoIP, IPTV, and WiFi QoE at various network levels. Remote monitoring of the quality of their network and identification of issues which can lower the customer's QoE. Our proposed solution will help expedite the smart cities infrastructure and digital solutions with the aid of next generation networks. Abstract: Total internet traffic has witnessed unprecedented growth over the last two decades and this exponential trend is projected to continue. Future cities are expected to be smart and billions of devices will be connected forming a network. The emergence of the Internet of Things proffers to link sensors enabled digital devices with the internet thus offering new services in the context of smart cities. In this regard, it is crucial for the internet service providers (ISPs) to observe/monitor their end-to-end network performance and identify any possible service degradation(s) as the goal of smart cities can only be realized through good quality internet. In this paper, we demonstrate our hardware-software co-designed quality of experience (QoE) management solution for ISPs. Our system is capable of monitoring and reporting the web, video, VoIP, IPTV, and WiFi QoE at various network levels. We experimentally tested our solution at appropriate network locations and demonstrated QoE and latency results for one of the leading ISP of South Asia. Our solution enables the ISPs to remotely monitor the quality of their network and identify any issue(s) which can lower the customer's QoE. As the internet is the backbone of smart cities, we believe our proposed solution for QoE will help expedite the smart cities' infrastructure and solutions.